2006
DOI: 10.1002/jpln.200522013
|View full text |Cite
|
Sign up to set email alerts
|

Rice yield nutrient uptake as affected by cyanobacteria soil amendments—a pot experiment

Abstract: Rice production and cyanobacterial N in acid soil can be improved by liming. There is evidence that the organic amendments can increase the soil pH. The aim of this study was to find appropriate combination of soil amendments and cyanobacteria capable for enhancing nutrient uptake and improving rice yield in acidic paddy soil. Three soil amendments (rice straw, sewage‐sludge composts, NPK) with and without inoculation of cyanobacteria were studied for rice plants (Oryza sativa L.) in a pot experiment. The slud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…Later, the microorganisms, soil biomass, are decomposed by other microbes, and then the nitrogen will be mineralized to ammonium followed by nitrification to nitrate. It has been observed that from the results in this experiment, the marked increase of the total N in soil under inoculated pot may be attributed not only to high population of microorganism and its activity but also to some of bacteria able to fix the atmospheric nitrogen which add additional nitrogen to the soil [8]. Clay soil had higher level of soil NH 4 than the loamy soil.…”
Section: Effect Of Microbial Biomass and Nitrogen Sources On Nitrogenmentioning
confidence: 55%
See 4 more Smart Citations
“…Later, the microorganisms, soil biomass, are decomposed by other microbes, and then the nitrogen will be mineralized to ammonium followed by nitrification to nitrate. It has been observed that from the results in this experiment, the marked increase of the total N in soil under inoculated pot may be attributed not only to high population of microorganism and its activity but also to some of bacteria able to fix the atmospheric nitrogen which add additional nitrogen to the soil [8]. Clay soil had higher level of soil NH 4 than the loamy soil.…”
Section: Effect Of Microbial Biomass and Nitrogen Sources On Nitrogenmentioning
confidence: 55%
“…The soil samples were air-dried, ground and sieved using a 0.5 mm stainless sieve, and stored under laboratory condition until being analyzed. The total content of nitrogen and carbon in the soil and plant was determined using the Sumi-Graph CHN-21 analyzer at Tottori University Japan [8,24].…”
Section: Soil Analysesmentioning
confidence: 99%
See 3 more Smart Citations